BACTERIAL STUDY OF BACTERIA SPECIES CAUSING URINARY TRACT INFECTION IN KIRKUK CITY. - Marwa Jassim Mohammed (Scholar Express Journals, 2021)
When speaking of the human urinary tract, we are referring to an integrated system of collection and emptying, which consists of Kidneys, ureters, bladder and urethra , Urinary tract infection affects both genders and it is an infection affecting infants and children. The current study aimed to investigate the bacterial species that cause urinary tract infection, where 65 urine samples were collected from patients of different ages and both gender. The results showed that E.coli, a Gram-negative bacteria, was the main cause of UTI with a percentage of 30%, followed by Gram-positive bacteria, Staphylococcus aureus, with a percentage of 24%.The lowest rate of infection was by Proteus mirabilis bacterium at 4%.
Keywords: UTI; E. coli; Staphylococcus; Drug sensitivity